HIGH POLITICS MUHAMMADIYAH - Marratu Fahri (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2023)
After the reform, many fundamental changes regarding the rights and obligations of the people underwent redefinition. Previously, very few political rights were enjoyed by the people. In the midst of reform, it seemed as if the people were allowed to determine their own political rights, but the awareness of their obligations actually receded. Such an open political condition allows many parties to form political parties, the people have broad political channels through various platforms. Likewise, Mass Organizations and NGOs of various forms grow like mushrooms in the rainy season. Some of them even go beyond their roles and functions to a certain extent, as if they have become a formal political institution like a political party or at least become a